Correlation Between the Microstructure of Copper Oxide Thin Film and Its Gas Sensing Response - Ahmad Faizal, Mohd Zain; Jia, Wei Low; Nafarizal, Nayan; Mohd Zainizan, Sahdan; Mohd Khairul, Ahmad; Ali Yeon, Md Shakaff; Ammar, Zakaria (2014)
Copper oxide gas sensor was prepared on silicon wafer by sputtering of copper target at different oxygen flow rate of 0, 4, 8 and 16 sccm using RF magnetron sputtering technique. Argon flow rate, RF power, working pressure and substrate bias voltage were fixed at 50 sccm, 400 W, 22.5 mTorr and −40 V, respectively. The effect of varying the oxygen flow rate towards the time response of the copper oxide gas sensor was investigated. In addition, the influence of the copper oxide thin films microstructure and I-V characteristic was also considered. Based on the result, copper oxide gas sensor fabricated at 8 sccm of oxygen flow rate provide a better response of 0.024V/s compare to those fabricated at 0, 4 and 16 sccm.